Ferroptosis and EMT resistance in cancer: a comprehensive review of the interplay - Zhang, Huiming; Chen, Naifeng; Ding, Chenglong; Zhang, Huinan; Liu, Dejiang; Liu, Shuang (Frontiers in Oncology, 2024)
Ferroptosis differs from traditional cell death mechanisms like apoptosis, necrosis, and autophagy, primarily due to its reliance on iron metabolism and the loss of glutathione peroxidase activity, leading to lipid peroxidation and cell death. The dysregulation of iron metabolism is a hallmark of various cancers, contributing to tumor progression, metastasis, and notably, drug resistance. The acquisition of mesenchymal characteristics by epithelial cells is known as Epithelial-Mesenchymal Transition (EMT), a biological process intricately linked to cancer development, promoting traits such as invasiveness, metastasis, and resistance to therapeutic interventions. EMT plays a pivotal role in cancer progression and contributes significantly to the complex dynamics of carcinogenesis.Research findings indicate that mesenchymal cancer cells exhibit greater susceptibility to ferroptosis compared to their epithelial counterparts. The induction of ferroptosis becomes more effective in eliminating drug-resistant cancer cells during the process of EMT. The interplay between ferroptosis and EMT, a process where epithelial cells transform into mobile mesenchymal cells, is crucial in understanding cancer progression. EMT is associated with increased cancer metastasis and drug resistance. The review delves into how ferroptosis and EMT influence each other, highlighting the role of key proteins like GPX4, which protects against lipid peroxidation, and its inhibition can induce ferroptosis. Conversely, increased GPX4 expression is linked to heightened resistance to ferroptosis in cancer cells. Moreover, the review discusses the implications of EMT-induced transcription factors such as Snail, Zeb1, and Twist in modulating the sensitivity of tumor cells to ferroptosis, thereby affecting drug resistance and cancer treatment outcomes. Targeting the ferroptosis pathway offers a promising therapeutic strategy, particularly for tumors resistant to conventional treatments. The induction of ferroptosis in these cells could potentially overcome drug resistance. However, translating these findings into clinical practice presents challenges, including understanding the precise mechanisms of ferroptosis induction, identifying predictive biomarkers, and optimizing combination therapies. The review underscores the need for further research to unravel the complex interactions between ferroptosis, EMT, and drug resistance in cancer. This could lead to the development of more effective, targeted cancer treatments, particularly for drug-resistant tumors, offering new hope in cancer therapeutics.